Participatory mapping of the forest community stakeholders in Europe focusing on forest genetic resources, forest reproductive material, and protected forests - T. Rogelja; L. Secco; F. Lefèvre; E. Beuker; M. Westergren; B. Fady; S.C. González-Martínez; T. Myking; L.E. Pâques; C. Rellstab; G.G. Vendramin; T. Chauvin; et al. (Trees, Forests and People, 2025)
The genetic diversity of forest trees, as provided by Forest Genetic Resources (FGR) and being the basis for the production of Forest Reproductive Material (FRM), is fundamental for maintaining forest resilience, adaptability, health, productivity, and biological diversity. Despite their importance, stakeholder governance of genetic diversity remains under-studied. This study aims to address this gap by mapping the forest stakeholder landscape FGR governance. Using the Quadruple Helix Approach, we categorised stakeholders into academia, industry, government, and civil society identifying relevant sub-communities. The mapping process involved iterative revisions through expert consultations, workshops, and literature scoping. Results show that the FGR sub-community is situated between strict conservation efforts and applied forestry, supporting both genetic conservation and productive forest management. The FRM sub-community, dealing specifically with the production and deployment of FRM, prioritises tree breeding, seed production, and afforestation/reforestation programmes. Meanwhile, the Protected Forests (PF) sub-community focuses on strict nature conservation, advocating minimal human intervention while facing pressures from resource extraction, tourism, and land-use conflicts. The diverging attitudes and values of close-to-nature forest management, intensive forestry, and strict protections, respectively, exist within same stakeholder groups, as well as among different ones, and are spanning all sub-communities. The study uncovers key tensions such as competing land-use priorities between forestry, agriculture, infrastructure and energy sectors, limited flow of knowledge between stakeholder categories and governance misalignments between local, national, and international regulations. The findings are particularly relevant for policymakers, forest managers, forest nurseries, conservation organisations, and industry stakeholders to balance conservation with sustainable forest utilisation. By integrating stakeholder perspectives and highlighting key governance challenges, this study shows where a common ground can be found and where divergent opinions are strong, opening the way for more integrated strategies and policies.